Topical Application of Centella asiatica in Wound Healing: Recent Insights into Mechanisms and Clinical Efficacy - Katarzyna Witkowska; Magdalena Paczkowska-Walendowska; Ewa Garbiec; Judyta Cielecka-Piontek (MDPI AG, 2024)
Centella asiatica, widely known as Gotu kola, is a traditional herb celebrated for its benefits in skin health and wound healing. Recent research has provided new insights into its efficacy, particularly through topical applications. This review highlights the plant's mechanisms, focusing on its active compounds such as asiaticoside, madecassoside, asiatic acid, and madecassic acid, which enhance collagen synthesis, modulate inflammation, and offer antioxidant protection. Clinical trials have been collected and summarized that innovative delivery systems, such as hydrogels, nanostructures or microneedles, can accelerate wound healing, reduce wound size, and improve recovery times in various wound types, including diabetic ulcers and burns. Future research will likely refine these technologies and explore new applications, reinforcing the role of C. asiatica in contemporary wound care. Advances in formulation and delivery will continue to enhance the plant's therapeutic potential, offering promising solutions for effective wound management.